The Impact Of Ethical Leadership And Islamic Work Ethics On Learning Organization In Malaysian Public Higher Education Institutions: The Moderating Role Of Psychological Safety - Shamyl Shalyzad Shamsuddin; Abdul Rahim Zumrah; Nik Suhaida Nik Abdul Majid (Asian Scholars Network (ASNet), 2025)
Indexed by MyJurnal (Tier 3)